Non-Linear Reconstruction Of Dielectric Target In Dispersive Media Featuring Ultra-Wide Band Sensing And Gradient Minimization - Zanoon, Tareq Faisal (2011)
In the last decade, there has been a growing interest in using UWB signals for microwave tomography. The diversity of frequencies in the illuminating UWB signal offers a unique combination enabling scattering of very long to very short wavelengths, and thus, collecting more information about the target. While microwave in general posses properties of preference for many imaging applications, inversion algorithms leading to recovery of the dielectric profile are complex in their nature, and vulnerable to noisy experimental conditions and environment.